2010
DOI: 10.1016/j.mod.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling via angiopoietin1 is required for developmental vascular stability

Abstract: The molecular pathways by which newly formed, immature endothelial cell tubes remodel to form a mature network of vessels supported by perivascular mural cells are not well understood. The zebrafish iguana (igu) genetic mutant has a mutation in the daz-interacting protein 1 (dzip1), a member of the hedgehog signaling pathway. Loss of dzip1 results in decreased size of the cranial dorsal aortae, ultrastructural defects in perivascular mural cell recruitment and subsequent hemorrhage. Although hedgehog signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…Besides the typical ciliary phenotypes reported in the previous study , we further found that the mRNA splicing inhibited-zebrafish had disrupted vasculature systems (Figure 4(c)). These malformed blood vessels are also known ciliary defects (Lamont et al 2010;Goetz et al 2014), and thus our data suggest that mRNA splicing is involved in a ciliogenesis control.…”
Section: Inhibition Of Mrna Splicing Causes Ciliary Defectssupporting
confidence: 61%
“…Besides the typical ciliary phenotypes reported in the previous study , we further found that the mRNA splicing inhibited-zebrafish had disrupted vasculature systems (Figure 4(c)). These malformed blood vessels are also known ciliary defects (Lamont et al 2010;Goetz et al 2014), and thus our data suggest that mRNA splicing is involved in a ciliogenesis control.…”
Section: Inhibition Of Mrna Splicing Causes Ciliary Defectssupporting
confidence: 61%
“…Mural cells of the AMA and DA express early VSMC markers (62,65,77) and the pericyte marker PDGF receptor b (pdgfrb) in the DA (74). However, these cells lack myofilaments and cytoskeletal plaques, which is consistent with undifferentiated and noncontractile cells (39,48,62). Due to low circulatory pressures in fish (62,77), AMA mural cells may not directly impact on vascular tone but rather perform angiogenic and endocrine functions.…”
Section: Discussionmentioning
confidence: 99%
“…27 Interestingly, previous work showed that treatment with cyclopamine, an antagonist of the Hedgehog pathway, causes ICH in zebrafish embryos reminiscent of the phenotype that we observed in IFT mutants, suggesting that this pathway may be important for developmental vascular integrity. 28 To investigate whether the Hedgehog pathway is associated with cilia-associated ICH, we first identified a suboptimal regimen of cyclopamine treatment by titrating the dosage and time window. Treatment with 25-30 mmol/L cyclopamine from 25 hpf did not change the embryo morphology significantly (Figure 4, A and B), which allowed us to identify mutant embryos unequivocally on the basis of their body curvature phenotype.…”
Section: Defective Hedgehog Signaling Is a Major Cause Of Ich In Ift mentioning
confidence: 99%